Мікроміцети в питній воді та шляхи її знезараження - Гончарук, В.В.; Руденко, А.В.; Савлук, О.С.; Коваль, Є.З.; Саприкіна, М.М. (Видавничий дім "Академперіодика" НАН України, 2008)
Such microscopic fungi as Cladosporium cladosporioides, Aspergillus niger, Penicillium gri-scofulvum, and others are isolated from the pipe water of Kyiv and identified as a disease-causing agent. It is established that the methods of coagulation and flocculation under the developed treatment modes can provide the total disinfection of water from these pathogenic organisms.